Development of Calculation Technique by Designing the Radiative Recu- perators Advanced in Frame of EUREKA Program - Sevcsik, M.; Kapros, T.; Sandor, P.; Soroka, B.S. (Энерготехнологии и ресурсосбережение, 2014)
The EUREKA project «REPLACE NG» is focused on development and application of radiative (radiative-convective) recuperator of advanced design for heat recovery of flue gases by combustion the fuels including those of low calorific value (LCV gases) in the industrial furnaces of various types. It was supposed that the recuperators are suitable for preheating the flows of combustion air or LCV gases. Recuperators of both purposes could be used by installation at the furnaces fired with LCV gases. Mentioned equipment — recuperator of RRD type — was developed by Gas Institute of NASU (Ukraine). It was supposed accordingly preliminary program and schedule to involve Co. TUKI (Hungary) as the project partner for testing the recuperator arranged at the bell type furnace of Cold Rolling Mill Plant of ISD DUNAFERR Group under the furnace firing with different process gases (alternative fuels) originated by several metallurgical productions. The present paper demonstrates the proposed calculation technique suitable for comparison the thermal state of the new type heat exchangers and the radiative recuperators of traditional wide spread design basing upon computation of heat exchange processes within parallel-current and counter-current flows. The system of simplified differential one-dimensional heat balance and heat exchange equations was composed and used as the computation background. The computation model provides an opportunity to analyse an influence of heat transfer coefficients, mass and volume flow rates and heat fluxes by process of an air preheating due discovering and application the generalizing auxiliary dimensionless parameters. The advantages of new approach to the recuperators designing even by neglecting of an enhancement of heat transfer intensity from both sides of heat exchange surface(s) or from both media flows are connected with increase the heat exchange surface in case of recuperator of RRD type in comparison with ordinary one-stage radiative recuperators. Application of secondary (intermediate) adiabatic emitters arranged in channels for flue gases and air (or LCV gas) flows provides the additional opportunities. Проект «REPLACE NG» («Замещение природного газа») направлен на разработку и использование радиационного (радиацинно-конвективного) рекуператора новейшей конструкции для утилизации теплоты уходящих газов при сжигании топлив, включая низкокалорийные (LCV) газы, в промышленных печах различного назначения. В соответствии с планом работ предполагалось, что разрабатываемые рекуператоры должны быть пригодны для нагрева воздуха горения и самих низко калорийных газов. Рекуператоры двойного назначения могут использоваться при установке на печах, отапливаемых низкокалорийным газом. Упомянутое оборудование — рекуператор типа РРД — разработано Институтом газа НАНУ (Украина). В соответствии с предварительной программой и графиком работ было намечено привлечение компании «ТЮКИ» (Венгрия) в качестве партнера по проекту на разных этапах, в частности, при испытаниях рекуператора, монтируемого с этой целью на колпаковой печи в цехе холодной прокатки комбината «ИСД ДУНАФЕРР». В ходе испытаний предусмотрено опробовать отопление печи различными технологическими газами металлургических производств (альтернативным топливом). В настоящей работе представлен вывод расчетных зависимостей, обеспечивающих прямое сравнение теплового состояния теплообменника нового типа и радиационных рекуператоров традиционной широко распространенной конструкции. Методика базируется на расчете процессов теплообмена в условиях прямо- и противоточного взаимного движения теплоносителей в каналах. Упрощенные дифференциальные уравнения теплового баланса и теплообмена для разных участков рекуператора были использованы в качестве базовой системы при получении расчетных зависимостей. Благодаря отысканию и применению обобщающих вспомогательных безразмерных параметров расчетная модель обеспечивает возможность анализа влияния коэффициентов теплообмена, массового и объемного потоков теплоносителей и тепловых потоков на результирующее температурное распределение в аппарате в процессе подогрева воздуха. Преимущества нового подхода к проектированию рекуператоров даже в случае пренебрежения ростом интенсивности теплообмена с обеих сторон теплообменной поверхности объясняются существенным увеличением области теплообмена (в случае рекуператора типа РРД) по сравнению с обычными одноходовыми радиационными рекуператорами. Использование вторичных (промежуточных) адиабатных излучателей в каналах для дымовых газов и воздуха (или потоков низкокалорийного газа) обеспечивает дополнительные возможности повышения подогрева воздуха (или низкокалорийного газа). Проект «REPLACE NG» («Заміщення природного газу») направлений на розробку та використання радіаційного (радіаційно-конвективного) рекуператора новітньої конструкції для утилізації теплоти викидних газів при спалюванні палив, у тому числі низькокалорійних (LCV) газів, у промислових печах різного призначення. У відповідності до плану робіт передбачалося, що розроблювані рекуператори мають бути придатними до нагріву повітря горіння та самих низькокалорійних газів. Рекуператори подвійного призначення можуть використовуватися при установці на печах, опалюваних низькокалорійним газом. Таке обладнання — рекуператор типу РРД — розроблено Інститутом газу НАНУ (Україна). У відповідності до наміченої програми та графіка робіт було намічено залучення компанії «ТЮКІ» (Угорщина) як партнера по здійсненню проекта на різних етапах, а саме: при випробуваннях рекуператора, змонтованого з цією метою на ковпаковій печі у цеху холодної прокатки комбінату «ІСД ДУНАФЕРР». Під час досліджень передбачено випробувати опалювання печі різними технологічними газами металургійного виробництва (альтернативним паливом). У цій роботі представлено виведення розрахункових залежностей, які забезпечуватимуть пряме порівняння теплового стану теплообмінника нового типу та радіаційних рекуператорів традиційної широко розповсюдженої конструкції. Методика базується на розрахунку процесів теплообміну в умовах прямо- та протиточного взаємного руху теплоносіїв у каналах. Спрощенні диференційні рівняння теплового балансу та теплообміну для різних зон рекуператора були використані як базова система при отриманні розрахункових залежностей. Завдяки відшуканню та застосуванню узагальнюючих допом іжних безрозмірних параметрів розрахункова модель забезпечує можливість аналізу впливу коефіцієнтів теплообміну, масового та об’ємного потоків теплоносіїв та теплових потоків на результуючий температурний розподіл в апараті у процесі підігріву повітря. Переваги нового підходу до проектування рекуператорів, навіть не беручи до уваги зростання інтенсивності теплообміну з обох сторін теплообмінної поверхні, поясняються суттєвим збільшенням області теплообміну (у разі рекуператора типа РРД) у порівнянні зі звичайними одноходовими радіаційними рекуператорами. Використання вторинних (проміжних) адіабатних випромінювачів у каналах для димових газів та повітря (чи потоків низькокалорійного газу) забезпечує додаткові можливості підвищення підігріву повітря (чи низькокалорійного газу).